2022
DOI: 10.3389/feart.2022.1044296
|View full text |Cite
|
Sign up to set email alerts
|

An unusually productive microearthquake sequence brings new insights to the buried active thrust system of Montello (Southeastern Alps, Northern Italy)

Abstract: In August 2021, an extremely productive seismic sequence took place in northeastern Italy. Within 1 month, we identified and localized 407 microearthquakes in the area monitored by the local Collalto Seismic Network. This is about 20 times the average monthly rate of events detected in the last decade; 92% of them are clustered near the village of Refrontolo at about 9 km depth (main event a ML2.5, MW2.4). None of the Refrontolo sequence earthquakes were felt by the population. The earthquakes, mostly identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…RSC is a high‐resolution permanent network, consisting of a cluster of high‐sensitivity stations deployed right above the reservoir, fully operating since 2012 (Priolo et al., 2015). Over the years, RSC has provided a detailed picture of the Montello area background seismicity, so far poorly known, and has demonstrated that the underground storage activities are not related to such microseismic events (Peruzza et al., 2022; Romano et al., 2019). The RSC catalog used contains 1635 earthquakes (−0.8 ≤ M L ≤ 4.5) localized with an optimized 1D velocity model in the period January 2012 to October 2017.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RSC is a high‐resolution permanent network, consisting of a cluster of high‐sensitivity stations deployed right above the reservoir, fully operating since 2012 (Priolo et al., 2015). Over the years, RSC has provided a detailed picture of the Montello area background seismicity, so far poorly known, and has demonstrated that the underground storage activities are not related to such microseismic events (Peruzza et al., 2022; Romano et al., 2019). The RSC catalog used contains 1635 earthquakes (−0.8 ≤ M L ≤ 4.5) localized with an optimized 1D velocity model in the period January 2012 to October 2017.…”
Section: Methodsmentioning
confidence: 99%
“…After the strong seismic events in the Friuli area, east of the Montello hill, in 1976, the eastern southalpine mountain front was explored from a seismotectonic point of view and the seismic sources defined, based on the available geological constraints (e.g., Burrato et al., 2008; Galadini et al., 2005; Peruzza, Poli, et al., 2002; Peruzza, Romano, et al., 2002). Several scholars analyzed its geodetic deformation in order to assess the seismogenic potential of the Montello structure (e.g., Barba et al., 2013; Cheloni et al., 2014; D’Agostino et al., 2005; Danesi et al., 2015; Serpelloni et al., 2016).…”
Section: Introductionmentioning
confidence: 99%